WHO ICF as an assessment tool for evaluation of self-care activities of the child with cerebral palsy - Avetisyan, Mery
The study was conducted in two stages. At the first stage, quantitative methods were chosen as methodologies, since the object that is studied by this method is a quantitative unit, which in the future allows to draw conclusions, based on the results, using certain numerical models to develop or confirm new hypotheses, or/and refute existing ones. At the second stage, a qualitative study was conducted on the basis of the results of the first stage, accordingly developing recommendations on ergotherapy for each code issue. According to the study results, in today's Armenia, it is possible to issue all the problems that children with Cerebral Palsy face in self-care and life by using certain assessing tools of occupational therapy. In this case, the study shows that the evaluation of the World Health Organization International Classification of Functioning and Disability, Children and Youth (2008) allows to observe and issue the existing problems of this sphere in a more accurate and comprehensive way․ It also provides an objective basis for identifying the problems in the field of children's self-service and life, which, in its turn, allows the occupational therapist to conduct a detailed assessment to find out which self-service actions are available to the child, to what extent the child’s actions and personal roles are compatible with the current state of the disease, and to what extent the actions correspond to their age.
Keywords: Medicine